Identifying Key Biomarkers in Pediatric Pulmonary Hypertension: An Investigative Approach - Farida Mindubayeva; Lyudmila Akhmaltdinova; Mariya Ospanova; Bibigul Tukbekova; Zhanat Bolatbekuly; Yuliya Niyazova; Yelena Salikhova; Olga Avdienko; Meruert Akhmetova (MDPI AG, 2024)
This study assesses the utility of early biomarkers-5-hydroxyindoleacetic acid (5-HIAA) and insulin-like growth factor 1 (IGF-1)-for diagnosing and monitoring pulmonary hypertension (PH) in children with congenital heart defects (CHD). Due to the risks associated with invasive diagnostics, such as right heart catheterization, non-invasive biomarkers provide a safer alternative for early PH detection. This cohort-based study utilized blood and urine samples to measure 5-HIAA and IGF-1 levels via enzyme immunoassays. Our findings revealed significant changes in 5-HIAA concentrations across various biological matrices, supporting its potential as a diagnostic tool. Specifically, altered levels in urine and plasma reflect its role in serotonin metabolism and vascular remodeling in PH. IGF-1 levels were notably reduced in plasma, suggesting its involvement in PH pathophysiology. ROC analysis confirmed the diagnostic efficacy of these biomarkers, particularly 5-HIAA's high specificity and sensitivity. In conclusion, 5-HIAA and IGF-1 levels correlate well with PH, underscoring their diagnostic value for early PH detection in children with CHD.